2009
DOI: 10.1089/apc.2008.0240
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Community-Associated Methicillin-Resistant Staphylococcus aureus Infections among HIV-Infected Persons: Incidence and Risk Factors

Abstract: Community-associated MRSA (CA-MRSA) infections are well described among the general population, but little is known regarding the incidence of and predictors for recurrent CA-MRSA infections among HIV-infected persons. We retrospectively evaluated HIV-infected patients seen at the Naval Medical Center San Diego from January 1, 2000 to June 30, 2007 for wound culture-proven MRSA infections defined as community-associated based on CDC criteria. Data on skin/soft tissue infections (SSTIs) following an initial CA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 17 publications
1
48
0
3
Order By: Relevance
“…Among 959 Greek Air Force employees in 2004 to 2005, 9 (0.94%) had nasal colonization with MRSA, and 2 of the 9 had no previous known exposure to the health care system (461). 3 , and the HIV viral load was Ͻ1,000 copies/ml in 48% of the patients; 71% of the patients were receiving antiretroviral therapy at the time of their infections (195). A study performed in 2000 to 2003 demonstrated a steady rise in the incidence of MRSA infections among patients at an adult HIV clinic in San Diego from 2 to 5 per 100 patients in a 6-month period (589).…”
Section: Military Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 959 Greek Air Force employees in 2004 to 2005, 9 (0.94%) had nasal colonization with MRSA, and 2 of the 9 had no previous known exposure to the health care system (461). 3 , and the HIV viral load was Ͻ1,000 copies/ml in 48% of the patients; 71% of the patients were receiving antiretroviral therapy at the time of their infections (195). A study performed in 2000 to 2003 demonstrated a steady rise in the incidence of MRSA infections among patients at an adult HIV clinic in San Diego from 2 to 5 per 100 patients in a 6-month period (589).…”
Section: Military Populationsmentioning
confidence: 99%
“…Culture results were available for only some recurrent lesions; of 14 patients with a CA-MRSA index SSTI and a recurrence, 7 (50%) had a culture-confirmed CA-MRSA SSTI recurrence. Recurrence was associated with an HIV viral load of Ͼ1,000 copies/ml (OR, 0.14; P ϭ 0.03 for patients with a viral load of Ͻ1,000 copies/ml), and there was a trend for an increased risk of recurrence if an incision-and-drainage procedure was not performed for the index CA-MRSA SSTI (OR, 0.19; P ϭ 0.07) (195).…”
Section: Patients With Sstismentioning
confidence: 99%
“…Immunocompromised hosts with defects in Th17 expansion, including HIV/AIDS patients and individuals with hyperimmunoglobulin E syndrome (HIES, or Job's syndrome), are susceptible to opportunistic infections by Staphylococcus aureus, Haemophilus influenzae, and Streptococcus pneumoniae, among others (15,31,59,72). In HIV infection, Th17 cells are preferentially depleted from the gastrointestinal lymphocyte compartment, despite the unresponsiveness of this subset to viral antigens (9).…”
Section: Extracellular Bacterial Pathogensmentioning
confidence: 99%
“…Recent studies have demonstrated that microbiota composition defines the behavior and virulence gene expression of primary pathogens (17,30) and host susceptibility to infection (16,30). Hence, a first step toward understanding the contribution of the airway microbiome to recurrent pneumonia in HIV-infected patients (12,27,43) is the identification of organisms present, despite antimicrobial treatment, both in the airway and in the oral cavity, since the latter has long been recognized as a potential microbial reservoir for reinfection of the airways (32,36). Identification of members of the microbiota that is present despite therapeutic intervention provides valuable insights into the efficacy of such treatments and identifies species that may contribute to subsequent pulmonary episodes.…”
mentioning
confidence: 99%